2001
DOI: 10.1002/ijc.1508
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the HER2NEU‐derived tumor antigen GP2 improves induction of GP2‐reactive cytotoxic T lymphocytes

Abstract: GP2 (IISAVVGIL), the p654 -662 HER2/neu-derived tumor antigen, induces HLA-A2-restricted cytotoxic T lymphocytes (CTL) reactive to various epithelial cancers. The binding affinity of GP2 for HLA-A2, however, is very low. To improve the immunogenicity of GP2, we tested 10 different amino acid substitutions into GP2 at the C-and N-terminus. Five out of 10 modified peptides, especially those containing phenylalanine at position 1 (1F), showed a significantly improved binding affinity to HLA-A2. 1F-based modified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 29 publications
2
13
0
Order By: Relevance
“…These results are in accordance with several reports showing a relationship between MHC class I binding and in vivo and in vitro immunogenicity [35][36][37][38][39]. Tanaka et al [40] reported that modified peptides not only increased the binding affinity to HLA-A2 but also improved recognition of native peptide. However, it needs to be further investigated whether or not it can also promote the expansion or proliferation of Ag-specific CTL.…”
Section: Discussionsupporting
confidence: 92%
“…These results are in accordance with several reports showing a relationship between MHC class I binding and in vivo and in vitro immunogenicity [35][36][37][38][39]. Tanaka et al [40] reported that modified peptides not only increased the binding affinity to HLA-A2 but also improved recognition of native peptide. However, it needs to be further investigated whether or not it can also promote the expansion or proliferation of Ag-specific CTL.…”
Section: Discussionsupporting
confidence: 92%
“…The discrepancies between the predicted affinity of the peptides and their corresponding membrane stabilization ability of the HLA-A3 molecule may be due to the fact that the binding affinity of the peptide is determined by both the binding motifs as well as the 3-dimentional structure of the peptide in the MHC Class I groove. 23,24 Because it has been shown previously that the affinity of a given peptide to a MHC class I molecule does not necessarily correlate with its ability to generate CD8ϩ CTLs, 25,26 we used all the peptides to examine the profile of CD8ϩ CTL reactivity in 5 HLA-A3ϩ breast cancer patients and 4 HLA-A3ϩ healthy female controls by means of an ELISPOT assay as described. As shown in Table V showed CD8ϩ CTL reactivity against peptides MamA-3.1 and Mam-A3.3 and 2 patients (40%) showed CD8ϩ CTL reactivity against peptide Mam-A3.8.…”
Section: Identification Of Hla-a3-restricted Cd8ϩ Ctl Epitopes Derivementioning
confidence: 99%
“…To place the binding score on an appropriate scale, the structures of a peptide known to be a strong HLA-A2 binder (GILGFVFTL; derived from the influenza matrix virus [35]) and a peptide known as a weak HLA-A2 binder (IISAVVGIL; the Gp2 peptide from HER2/Neu [12,13]) were predicted using PePSSI. Eqs.…”
Section: Pepssi Binding Score Equationmentioning
confidence: 99%
“…For peptide vaccination, the antigenic peptide is derived from a protein that is overexpressed in the targeted tumor cells [11]; one of the best known examples of this is the Gp2 peptide fragment of the HER2/Neu protein, which is commonly overexpressed in breast cancer [12,13]. Therefore, prediction of whether a peptide will bind to a particular human MHC molecule is of importance for development of peptide-based vaccines [11], and computational approaches have been created to identify such peptides.…”
Section: Introductionmentioning
confidence: 99%